Electronic vs. Paper Voter Guides and Citizen Knowledge: A Randomized Controlled Trial. Issue 3 (2nd July 2020) - Cann, Damon M.
ABSTRACT: Scholars are generally aware of a lack of citizen knowledge about politics in the United States. One commonly suggested remedy is the production of nonpartisan voter guides to provide voters a simple and low-cost information source to help inform voters. One of the more significant variations across states is whether the voter guide is provided in a hard-copy format or distributed on the internet. This paper explores the results of a randomized controlled trial comparing a group of registered voters in Utah who received a hard-copy of a paper voter guide against a group registered voters who received a postcard inviting them to view their voter guide online. Results show few statistically significant differences between the paper guide group and the postcard group in knowledge and turnout, and those that are observed slightly favor the postcard/online group.